Alice Waters cooks up a food revolution - Stanley, Diane (Simon & Schuster Books for Young Readers, 2022)
"The delicious story of pioneering chef Alice Waters who changed the way America eats and kickstarted the organic food movement. A pioneer of the slow and organic food movements, she is also known for creating Edible Schoolyard, a project that involves kids in the growing of their own food."--